Ketamine for management of acute exacerbations of asthma in children - Jat, Kana R (Cochrane Database Syst Rev, 2012)
BACKGROUND: Asthma is the most common chronic disease in children, and children with asthma frequently visit the paediatric emergency departments with acute exacerbations. Some of these children fail to respond to standard therapy (aerosol beta(2)‐agonist with or without aerosol anticholinergic and oral or parenteral corticosteroids) for acute asthma leading to prolonged emergency department stay, hospitalisation, morbidity (e.g. barotrauma, intubation) and death, albeit rarely. Ketamine may relieve bronchospasm and is a potentially promising therapy for children with acute asthma who fail to respond to standard treatment. OBJECTIVES: To evaluate the efficacy of ketamine compared to placebo, no intervention or standard care for management of severe acute asthma in children who had not responded to standard therapy. SEARCH METHODS: We identified trials from the Cochrane Airways Group Specialised Register of trials (CAGR) and ClinicalTrials.gov. We reviewed reference lists of all primary studies and review articles for additional references. We contacted authors of identified trials and asked them to identify other published and unpublished studies. The latest search was in July 2012. SELECTION CRITERIA: Randomised controlled trials comparing ketamine to placebo or standard care in children (up to 18 years of age) presenting with an acute asthma exacerbation who had not responded to standard therapy. DATA COLLECTION AND ANALYSIS: Two review authors independently selected studies. The data were extracted in pre‐defined proforma and were analysed independently by two review authors. The data analysis was performed using Review Manager 5.1. MAIN RESULTS: A single study enrolling 68 non‐intubated children was found eligible for inclusion in review. The study had low or unclear risk of bias. It demonstrated no significant difference in respiratory rate, oxygen saturation, hospital admission rate (odds ratio (OR) 0.77; 95% confidence interval (CI) 0.23 to 2.58) and need for mechanical ventilation between ketamine (0.2 mg/kg intravenous bolus over one to two minutes, followed by a 0.5 mg/kg per hour continuous infusion for two hours) and placebo group. There were no significant side effects of ketamine in the study. There was also no difference in need for other adjuvant therapy (OR 2.19; 95% CI 0.19 to 25.40) and in Pulmonary Index Score (mean difference (MD) ‐0.40; 95% CI ‐1.21 to 0.41) between the groups. AUTHORS' CONCLUSIONS: The single study on non‐intubated children with severe acute asthma did not show significant benefit and does not support the case studies and observational reports showing benefits of ketamine in both non‐ventilated and ventilated children. There were no significant side effects of ketamine. We could not find any trials on ventilated children. To prove that ketamine is an effective treatment for acute asthma in children, there is need for sufficiently powered randomised trials of high methodological quality with objective outcome measures of clinical importance. Future trials should also explore different doses of ketamine and its role in children needing ventilation because of severe acute asthma.